ALTERNATIVE TO TOPICAL DECONGESTANTS FOR SYMPTOMATIC TREATMENT OF CHILDREN'S ACUTE RHINITIS - E.Yu. Radtsig; N.V. Ermilova; N.V. Sapaeva; M.R. Bogomil'sky ("Paediatrician" Publishers LLC, 2007)
The article discusses mechanisms of occurrence and clinical course of children's acute rhinitis. It shows that traditionally, topical decongestants are used for curing acute rhinitis - a group of medications including sympathomimetics and selective ?1-adrenoceptor agonist. At the same time it is known that long time usage of decongestants is accompanied with serious side reactions (paresis of vessel walls of nasal mucous, medicament rhinitis, ETC). Besides, the poisoning frequency is high, especially among infants and younger school age children. An alternative curing method for acute rhinitis is an inhalation with volatile oils complex with bactericidal and bacteriostatic activity. Accordingly, this complex can be recommended as a safe and efficient means for curing and prophylaxis of acute rhinitis Key words: children, acute rhinitis, topical decongestants, volatile oils.